PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN YANG DIMEDIASI OLEH KEPUASAN KERJA STUDI PADA KARYAWAN PT. BANK MEGA, Tbk SEMARANG - 11.4202.0089, Joko Sulaksono (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to examine and analyze the effect of induvidu characteristics and job characteristics on organizational commitment mediated by job satisfaction of employees of PT. MEGA BANKS, Tbk Semarang. Population of 116 people, with census sampling technique and obtained a sample of 96 people. Techniques of data analysis: test validity by factor analysis, reliability testing with Alpha Chrombach, model test with Adjusted R2 and F-test, hypothesis testing with multiple linear regression and t test.The results: induvidu characteristics and job characteristics positive effect on organizational commitment, job satisfaction mediates the effect of job characteristics on organizational commitment and karaterisktik induvidu direct influence on organizational commitment is more effective than the influence of mediation. Keywords: Characteristic induvidu, job characteristics, organizational commitment, job satisfaction